Parasitic helminth infection of some freshwater fish species in suburban of Hanoi - Duc, Nguyen Van; Ha, Nguyen Van (Academia Journal of Biology, 2015)
In this study, 300 fishes belonging to 11 species and 6 families collected during the period 1999-2000, were investigated for parasitic helminth. 64.3% of these fishes were infected with density at 30.7 helminth/ fish (min-max: 1-280). The infection of Clarias fuscus (87,1% and 61,1 worms/host), Hypophthalmichthys molitrix (80,0% and 81,4 worms/host) and Ophiocephalus maculatus (70,0% and 40,6 worms/host) is higher than the one of other species. Anabas testudineus has highest rate (100,0%) but is infected with only nematodes at low density 5,3 worms/host. The infection rate and density of Monogenea is highest-31.7%, following by Trematoda-23,7%, Nematoda-16.7%, Cestoda – 12,0% and Acanthocephala-7.7%. The percentage of hosts infected with 3-4 helminth classes is very low, just only 7.8%. Most of the hosts are infected with 1 helminth class (65.8%) and 2 classes (26.4%).